Reference Charts of Fetal Biometric Parameters in 31, 476 Brazilian Singleton Pregnancies. (1st July 2014) - Araujo Júnior, Edward; Martins Santana, Eduardo Félix; Martins, Wellington P.; Júnior, Julio Elito; Ruano, Rodrigo; Pires, Claudio Rodrigues; Filho, Sebastião Marques Zanforlin
Abstract : Objectives: The purpose of this study was to establish reference charts of fetal biometric parameters measured by 2‐dimensional sonography in a large Brazilian population. Methods: A cross‐sectional retrospective study was conducted including 31, 476 low‐risk singleton pregnancies between 18 and 38 weeks' gestation. The following fetal parameters were measured: biparietal diameter, head circumference, abdominal circumference, femur length, and estimated fetal weight. To assess the correlation between the fetal biometric parameters and gestational age, polynomial regression models were created, with adjustments made by the determination coefficient ( R 2 ). Results: The means ± SDs of the biparietal diameter, head circumference, abdominal circumference, femur length, and estimated fetal weight measurements at 18 and 38 weeks were 4.2 ± 2.34 and 9.1 ± 4.0 cm, 15.3 ± 7.56 and 32.3 ± 11.75 cm, 13.3 ± 10.42 and 33.4 ± 20.06 cm, 2.8 ± 2.17 and 7.2 ± 3.58 cm, and 256.34 ± 34.03 and 3169.55 ± 416.93 g, respectively. Strong correlations were observed between all fetal biometric parameters and gestational age, best represented by second‐degree equations, with R 2 values of 0.95, 0.96, 0.95, 0.95, and 0.95 for biparietal diameter, head circumference, abdominal circumference, femur length, and estimated fetal weight. Conclusions: Fetal biometric parameters were determined for a large Brazilian population, and they may serve as reference values in cases with a high risk of intrauterine growth disorders.